2013
DOI: 10.1145/2501654.2501661
|View full text |Cite
|
Sign up to set email alerts
|

A survey of trust in social networks

Abstract: Web-based social networks have become popular as a medium for disseminating information and connecting like-minded people. The public accessibility of such networks with the ability to share opinions, thoughts, information, and experience offers great promise to enterprises and governments. In addition to individuals using such networks to connect to their friends and families, governments and enterprises have started exploiting these platforms for delivering their services to citizens and customers. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
387
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(394 citation statements)
references
References 107 publications
3
387
1
3
Order By: Relevance
“…As a result, numerous empirical studies demonstrated that social networks do significantly influences the adoption decision of individual farmers [36][37][38][39][40]. Additionally, Sherchan et al [41] pointed out that the success of a social network for an individual relies on the level of trust between himself and other members in the same community. Without social trust, members may not feel comfortable expressing their opinions [42], which is makes it harder for individuals to receive and share information within their social network.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…As a result, numerous empirical studies demonstrated that social networks do significantly influences the adoption decision of individual farmers [36][37][38][39][40]. Additionally, Sherchan et al [41] pointed out that the success of a social network for an individual relies on the level of trust between himself and other members in the same community. Without social trust, members may not feel comfortable expressing their opinions [42], which is makes it harder for individuals to receive and share information within their social network.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Trust is transitive when it can be extended outside the scope of the two entities who established it [108]. However, this is not always the case.…”
Section: Intransitivitymentioning
confidence: 99%
“…In the Social Web, trust has to be studied from different aspects: data (or content), services (or applications), service providers (Web sites, organisations, governments or individuals) and service consumers (organisations or individuals). There has been already work reported in the literature covering these different aspects [11,19].…”
Section: Building Trusted Social Webmentioning
confidence: 99%
“…The emergence of the Social Web has spurred new research in the study of trust, and, recently, a number of trust models for social networks have been developed with a specific focus on social aspects of trust. Sherchan et al presented a comprehensive review of trust in social networks covering literature from both Computer Science and Social Sciences [19].…”
Section: Building Trusted Social Webmentioning
confidence: 99%